2018
DOI: 10.1007/s00221-018-5354-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of task symmetry on bimanual reach-to-grasp movements after cervical spinal cord injury

Abstract: Injury to the cervical spinal cord results in deficits in bimanual control, reducing functional independence and quality of life. Despite this, little research has investigated the control strategies which underpin bimanual arm/hand movements following cervical spinal cord injury (cSCI). Using kinematics and surface electromyography this study explored how task symmetry affects bimanual control, in patients with an acute cSCI (< 6 m post injury), as they performed naturalistic bimanual reach-to-grasp actions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Another noteworthy application is the study of compensatory movement strategies, which can be accompanied by the development of new muscle synergies [ 68 72 ]. Studies have commonly focused on these issues in the context of locomotion [ 3 , 27 , 34 , 35 , 73 98 ], while fewer studies focused on reach-to-grasp [ 99 107 ], and posture and balance [ 108 – 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another noteworthy application is the study of compensatory movement strategies, which can be accompanied by the development of new muscle synergies [ 68 72 ]. Studies have commonly focused on these issues in the context of locomotion [ 3 , 27 , 34 , 35 , 73 98 ], while fewer studies focused on reach-to-grasp [ 99 107 ], and posture and balance [ 108 – 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the visual control of bimanual movements is critical to normal everyday functioning and a major challenge for people who have impairments affecting their limb movements and/or vision. While previous studies have carefully investigated bimanual reaching movements in a range of different disorders, such as stroke (Jackson et al 2000;Punt et al 2005aPunt et al , 2005b), Parkinson's Disease (Castiello and Bennett 1997;Alberts et al 1998), and spinal cord injury (Britten et al 2018), we are not aware of any previous clinial studies that have investigated related visual control (i.e., eye movements) in these populations. Examining the visual control of bimanual movements in these populations, using approaches such as the one reported here would be informative and potentially allow coherent planning of rehabilitation strategies.…”
Section: Other Considerationsmentioning
confidence: 99%
“…The ability to coordinate the movement of both arms is essential to perform several activities of daily living [1], [2]. Despite this and the recent increase of interest in bilateral training programs [3], there is still limited information regarding the impact of a cSCI on bilateral upper limb neuromotor strategies [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…As for cSCI, a number of studies have adopted these techniques to objectively assess unilateral upper limb motor functions after the lesion [14], but little attention has been paid in using these technologies to comprehensively assess how cSCI affects the neuromotor abilities to perform coordinated bilateral movements. Studies by Britten et al [5], [15] have investigated the kinematic strategies adopted by cSCI individuals with incomplete lesions during coordinated reachto-grasp actions using a motion capture system. These studies found that these individuals retain a level of bilateral control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation